Management of the interactions’ risks when using phytomedicines in children - Temirova Оlena; Tarverdieva , Yana; Khaitovych , Mykola; Sova , Volodymyr; Kyrylchuk , Kateryna (The Ukrainian Scientific Medical Youth Journal, 2023)
phytomedicines play an essential role in the treatment of children’s diseases. Means of plant origin have a better safety profile, and due to the content of biologically active substances, they affect various links of pathological processes. However, data on the safety and efficacy of phytomedicines in children are limited and mostly derived from studies in adults. In addition, there are risks of pharmacokinetic and pharmacodynamic drug interactions. This study aims to study the risks of interaction when using phytomedicines and drugs in children. 100 parents participated in the study, most of whom had 1 or 2 children. An analysis of the pharmacotherapy courses of 50 children was also done. It has been established that parents when choosing medicines for children, consider their origin. Thus, more than 70 % of respondents consider phytomedicines to be safer for children and choose them for the treatment of acute respiratory viral infections (73 %), diseases of the throat (64 %), oral cavity (59 %), disorders of the gastrointestinal tract (28 %) and others. The phytomedicines of choice were: Chlorophyllip, Sinupret, Wormil Phyto, Proteflazid, Darsil, Cholelesan, etc., which 80 % of respondents used in combination with other medicinal products and without a doctor’s prescription (75 % of respondents). It was revealed that 10 % of respondents noted the appearance of undesirable reactions after using phytomedicines, in combination with other medicinal products in children, the manifestations of which were: allergic reactions, digestive disorders, headache/dizziness. Based on the results of the analysis of the pharmacotherapy courses, it was established that the children received an average of 5.8 ± 1.7 medicines. In particular, 28 % received 2 or more phytomedicines. In more than 40 % of children, the risks of pharmacokinetic interaction of phytomedicines with other medicinal products were revealed. Thus, 10% received herbal remedies based on St. John’s wort, which is a CYP3A4 inducer and reduces the effectiveness of albendazole, omeprazole, pantoprazole, and levocetirizine. While more than 30 % of children received products based on turmeric, silymarin, or grapefruit extract, which are strong CYP3A4 inhibitors. Risks of pharmacokinetic interaction at the stage of absorption (6 % of children) were associated with the use of flax and plantain seeds. In 10 % of children, the risk of pharmacodynamic interaction due to the use of thick eucalyptus leaf extract and an antiseptic agent was revealed. Therefore, when using phytomedicines in children, it is necessary to consider the risks of drug interactions. Phytomedicines can affect the pharmacokinetics of other drugs and change the realization of the clinical effect. When choosing and using phytomedicines the interaction of the doctor-pharmacist-parent is essential.